Genome-Wide Identification of BAHD Superfamily and Functional Characterization of Bornyl Acetyltransferases Involved in the Bornyl Acetate Biosynthesis in Wurfbainia villosa - Liang, Huilin; Lin, Xiaojing; Yang, Peng; Sun, Yewen; Wu, Qingwen; Alimujiang, Shamukaer; Zhao, Haiying; Ma, Dongming; Zhan, Ruoting; Yang, Jinfen (Frontiers in Plant Science, 2022)
Bornyl acetate (BA) is known as a natural aromatic monoterpene ester with a wide range of pharmacological and biological activities. Borneol acetyltransferase (BAT) catalyzing borneol and acetyl-CoA to synthesize BA is alcohol acetyltransferase, which belongs to BAHD super acyltransferase family, however, BAT responsible for the biosynthesis of BA has not yet been characterized. The seeds of Wurfbainia villosa (homotypic synonym: Amomum villosum) are rich in BA. Here we identified 64 members of BAHD gene family from the genome of W. villosa using both PF02458 (transferase) and PF07247 (AATase) as Hidden Markov Model (HMM) to screen the BAHD genes. Sixty-four WvBAHDs are distributed on 14 chromosomes and nine unanchored contigs, clustering into six clades; three WvBAHDs with PF07247 have formed a separated and novel clade: clade Ⅵ. Twelve candidate genes belonging to clade Ⅰ-a, Ⅰ-b and Ⅵ were selected to clone and characterize in vitro, among which eight genes have been identified to encode BATs acetylating at least one type of borneol to synthesize BA. All eight WvBATs can utilize (-)-borneol as substrates, but only five WvBATs can catalyze (+)-borneol, which is the endogenous borneol substrate in the seeds of W. villosa; WvBAT3 and WvBAT4 present the better catalytic efficiency on (+)-borneol than the others. The temporal and spatial expression patterns of WvBATs indicate that WvBAT3 and WvBAT4 are seed-specific expression genes, and their expression levels are correlated with the accumulation of BA, suggesting WvBAT3 and WvBAT4 might be the two key BATs for BA synthesis in the seeds of W. villosa. This is the first report on BAT responsible for the last biosynthetic step of BA, which will contribute to further studies on BA biosynthesis and metabolism engineering of BA in other plants or heterologous hosts.